A brief review on metal-curcumin complexes: synthesis approaches and their pharmaceutical applications - Kuber Kumar Bhagat; Rameshwar S. Cheke; Vivekanand D. Gavali; Prashant S. Kharkar; Nitin D. Arote (Discover Chemistry)
Abstract Curcumin is a key polyphenolic component of turmeric. In recent years, curcumin has gained considerable attention because of its diverse biological potential, such as its anti-inflammatory, antioxidant, and anticancer effects. A growing field of scientific research involves the development of metal-curcumin complexes, which represent novel strategies to enhance the therapeutic efficacy of curcumin. Curcumin usually reacts with the different metals by its diketone group to form the metal-curcumin complexes. It is reported that curcumin is capable of binding effectively with a variety of metal ions, including iron, zinc, cobalt, copper, gallium, chromium, platinum, manganese, nickel, palladium, rhenium, iridium, ruthenium, vanadium, gold, silver, mercury, aluminum, indium, tin, gadolinium, lanthanum and boron. This review article offers an extensive survey of recent progress in synthesis of diverse metal-curcumin complexes, covering a spectrum of metals, transition metals and some semi-metals curcumin complexes. Emphasizing the synthetic procedures of metal-curcumin complexes, this paper meticulously explores their characterization and illustrates their crucial involvement in medicinal applications and therapeutic interventions. Clinical trial number: Not applicable. Graphical abstract